(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
This article examines the paradigmatic consequences of the transformation of the marketing research system in the context of the digital economy. It is important to recognize that modern changes are not only technological in nature, but also mainly methodological. These changes are associated with changes in the logic of understanding the market, the role of data and the functions of marketing research in the business management system. It has been demonstrated that marketing research is evolving from a simple auxiliary tool for collecting information to a complex information and analytical system integrated into the process of making managerial decisions. The research methodology consists of systemic, evolutionary and comparative approaches, content analysis of scientific sources. The periodization of the development of marketing research has been carried out, which allowed us to identify key stages and corresponding methodological shifts. These shifts began with the empirical-statistical stage and ended with an integrated stage driven by artificial intelligence. It has been established that the transformation of the marketing research system occurs through a change in the dominant paradigms: positivist, interpretative, post-positivist and holistic. It is proven that the modern marketing research system is evolving into an integrated analytical framework that combines quantitative, qualitative and digital methods. The prevailing characteristics of the modern era are data-driven analytics, the use of big data, MarTech and AI, as well as the integration of real-time research into business management processes and operational marketing solutions.